Advantages and limitations of integrated flagellin adjuvants for HIV-based nanoparticle B-cell vaccines - Barnowski, Cornelia; Kadzioch, Nicole; Damm, Dominik; Yan, Huimin; Temchura, Vladimir (Pharmaceutics, 2019)
The great advantage of virus-like particle (VLP) nano-vaccines is their structural identity to wild-type viruses, ensuring that antigen-specific B-cells encounter viral proteins in their natural conformation. “Wild-type” viral nanoparticles can be further genetically or biochemically functionalized with biomolecules (antigens and adjuvants). Flagellin is a potent inducer of innate immunity and it has demonstrated adjuvant effectiveness due to its affinity for toll-like receptor 5 (TLR5). In contrast to most TLR ligands, flagellin is a protein and can induce an immune response against itself. To avoid side-effects, we incorporated a less inflammatory and less immunogenic form of flagellin as an adjuvant into HIV-based nanoparticle B-cell-targeting vaccines that display either the HIV-1 envelope protein (Env) or a model antigen, hen egg lysozyme (HEL). While flagellin significantly enhanced HEL-specific IgG responses, anti-Env antibody responses were suppressed. We demonstrated that flagellin did not activate B-cells directly in vitro, but might compete for CD4+ T-cell help in vivo. Therefore, we hypothesize that in the context of VLP-based B-cell nano-vaccines, flagellin serves as an antigen itself and may outcompete a less immunogenic antigen with its antibody response. In contrast, in combination with a strong immunogen, the adjuvant activity of flagellin may dominate over its immunogenicity.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Adjuvant; B-cell targeting; Flagellin; HIV-based VLP; Nano-vaccines

A pair of non‐competing neutralizing human monoclonal antibodies protecting from disease in a SARS‐CoV‐2 infection model - Peter, Antonia Sophia; Roth, Edith; Schulz, Sebastian; Fraedrich, Kirsten; Steinmetz, Tobit; Damm, Dominik; Hauke, Manuela; Richel, Elie; Müller-Schmucker, Sandra; Habenicht, Katharina Marie; Eberlein, Valentina; Issmail, Leila; et al. (European Journal of Immunology, 2021)
TRIANNI mice carry an entire set of human immunoglobulin V region gene segments and are a powerful tool to rapidly isolate human monoclonal antibodies. After immunizing these mice with DNA encoding the spike protein of SARS-CoV-2 and boosting with spike protein, we identified 29 hybridoma antibodies that reacted with the SARS-CoV-2 spike protein. Nine antibodies neutralize SARS-CoV-2 infection at IC50 values in the subnanomolar range. ELISA-binding studies and DNA sequence analyses revealed one cluster of three clonally related neutralizing antibodies that target the receptor-binding domain and compete with the cellular receptor hACE2. A second cluster of six clonally related neutralizing antibodies bind to the N-terminal domain of the spike protein without competing with the binding of hACE2 or cluster 1 antibodies. SARS-CoV-2 mutants selected for resistance to an antibody from one cluster are still neutralized by an antibody from the other cluster. Antibodies from both clusters markedly reduced viral spread in mice transgenic for human ACE2 and protected the animals from SARS-CoV-2-induced weight loss. The two clusters of potent non-competing SARS-CoV-2 neutralizing antibodies provide potential candidates for therapy and prophylaxis of COVID-19. The study further supports transgenic animals with a human immunoglobulin gene repertoire as a powerful platform in pandemic preparedness initiatives.

Calcium phosphate nanoparticle-based vaccines as a platform for improvement of HIV-1 env antibody responses by intrastructural help - Damm, Dominik; Rojas-Sánchez, Leonardo; Theobald, Hannah; Sokolova, Viktoriya; Wyatt, Richard T.; Überla, Klaus; Epple, Matthias; Temchura, Vladimir (Nanomaterials, 2019)
Incorporation of immunodominant T-helper epitopes of licensed vaccines into virus-like particles (VLP) allows to harness T-helper cells induced by the licensed vaccines to provide intrastructural help (ISH) for B-cell responses against the surface proteins of the VLPs. To explore whether ISH could also improve antibody responses to calcium phosphate (CaP) nanoparticle vaccines we loaded the nanoparticle core with a universal T-helper epitope of Tetanus toxoid (p30) and functionalized the surface of CaP nanoparticles with stabilized trimers of the HIV-1 envelope (Env) resulting in Env-CaP-p30 nanoparticles. In contrast to soluble Env trimers, Env containing CaP nanoparticles induced activation of naïve Env-specific B-cells in vitro. Mice previously vaccinated against Tetanus raised stronger humoral immune responses against Env after immunization with Env-CaP-p30 than mice not vaccinated against Tetanus. The enhancing effect of ISH on anti-Env antibody levels was not attended with increased Env-specific IFN-γ CD4 T-cell responses that otherwise may potentially influence the susceptibility to HIV-1 infection. Thus, CaP nanoparticles functionalized with stabilized HIV-1 Env trimers and heterologous T-helper epitopes are able to recruit heterologous T-helper cells induced by a licensed vaccine and improve anti-Env antibody responses by intrastructural help.
CRIS-Team Scopus Importer:2019-10-29
Keywords: B-cell targeting; HIV-1 env trimers; Intrastructural help; Nano-vaccines

Conjugation of native‐like hiv‐1 envelope trimers onto liposomes using edc/sulfo‐nhs chemistry: Requirements and limitations - Suleiman, Ehsan; Mayer, Julia; Lehner, Elisabeth; Kohlhauser, Bianca; Katholnig, Alexandra; Batzoni, Mirjam; Damm, Dominik; Temchura, Vladimir; Wagner, Andreas; Überla, Klaus; Vorauer‐uhl, Karola (Pharmaceutics, 2020)
The display of native‐like human immunodeficiency virus type 1 envelope (HIV‐1 Env) trimers on liposomes has gained wide attention over the last few years. Currently, available methods have enabled the preparation of Env‐liposome conjugates of unprecedented quality. However, these protocols require the Env trimer to be tagged and/or to carry a specific functional group. For this reason, we have investigated N‐(3‐Dimethylaminopropyl)‐N′‐ethylcarbodiimide/N‐ Hydroxysulfosuccinimide (EDC/Sulfo‐NHS) chemistry for its potential to covalently conjugate tag-free, non‐functionalized native‐like Env trimers onto the surface of carboxyl‐functionalized liposomes. The preservation of the liposome’s physical integrity and the immunogen’s conformation required a fine‐tuned two‐step approach based on the controlled use of β‐ mercaptoethanol. The display of Env trimers was strictly limited to activated liposomes of positive charge, i.e., liposomes with a positive zeta potential that carry amine‐reactive Sulfo‐NHS esters on their surface. In agreement with that, conjugation was found to be highly ionic strength‐ and pH-dependent. Overall, we have identified electrostatic pre‐concentration (i.e., close proximity between negatively charged Env trimers and positively charged liposomes established through electrostatic attraction) to be crucial for conjugation reactions to proceed. The present study highlights the requirements and limitations of potentially scalable EDC/Sulfo‐NHS‐based approaches and represents a solid basis for further research into the controlled conjugation of tag‐free, non-functionalized native‐like Env trimers on the surface of liposomes, and other nanoparticles.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Covalent conjugation; EDC/Sulfo‐NHS; HIV‐1; Intrastructural help; Liposomes; Native-like Env trimers; Particulate display; Pre‐concentration; Protein‐liposome conjugates; Tag‐free conjugation; Vaccines

Covalent coupling of HIV-1 glycoprotein trimers to biodegradable calcium phosphate nanoparticles via genetically encoded aldehyde-tags - Damm, Dominik; Kostka, K.; Weingärtner, Christoph; Wagner, Jannik; Rojas-Sánchez, L.; Gensberger-Reigl, Sabrina; Sokolova, V.; Überla, Klaus; Epple, M.; Temchura, Vladimir (Acta Biomaterialia, 2022)
The usage of antigen-functionalized nanoparticles has become a major focus in the field of experimental HIV-1 vaccine research during the last decade. Various molecular mechanisms to couple native-like trimers of the HIV-1 envelope protein (Env) onto nanoparticle surfaces have been reported, but many come with disadvantages regarding the coupling efficiency and stability. In this study, a short amino acid sequence (“aldehyde-tag”) was introduced at the C-terminus of a conformationally stabilized native-like Env. The post-translational conversion of a tag-associated cysteine to formylglycine creates a site-specific aldehyde group without alteration of the Env antigenicity. This aldehyde group was further utilized for bioconjugation of Env trimers. We demonstrated that the low acidic environment necessary for this bioconjugation is not affecting the trimer conformation. Furthermore, we developed a two-step coupling method for pH-sensitive nanoparticles. To this end, we conjugated aldehyde-tagged Env with Propargyl-PEG3-aminooxy linker (oxime ligation; Step-one) and coupled these conjugates by copper-catalyzed azide-alkyne cycloaddition (Click reaction; Step-two) to calcium phosphate nanoparticles (CaPs) functionalized with terminal azide groups. CaPs displaying orthogonally arranged Env trimers on their surface (o-CaPs) were superior in activation of Env-specific B-cells (in vitro) and induction of Env-specific antibody responses (in vivo) compared to CaPs with Env trimers coupled in a randomly oriented manner. Taken together, we present a reliable method for the site-specific, covalent coupling of HIV-1 Env native-like trimers to the surface of nanoparticle delivery systems. This method can be broadly applied for functionalization of nanoparticle platforms with conformationally stabilized candidate antigens for both vaccination and diagnostic approaches. Statement of significance: During the last decade antigen-functionalized nanoparticles have become a major focus in the field of experimental HIV-1 vaccines. Rational design led to the production of conformationally stabilized HIV-1 envelope protein (Env) trimers - the only target for the humoral immune system. Various molecular mechanisms to couple Env trimers onto nanoparticle surfaces have been reported, but many come with disadvantages regarding the coupling efficiency and stability. In this paper, we describe a highly selective bio-conjugation of Env trimers to the surface of medically relevant calcium phosphate nanoparticles. This method maintains the native-like protein conformation and has a broad potential application in functionalization of nanoparticle platforms with stabilized candidate antigens (including stabilized spike proteins of coronaviruses) for both vaccination and diagnostic approaches.
CRIS-Team Scopus Importer:2022-01-28
Keywords: Aldehyde-tag; Calcium phosphate nanoparticles; HIV-1 Env native-like trimers; Orthogonal; Site-specific coupling; Surface conjugation

Design and Functional Characterization of HIV-1 Envelope Protein-Coupled T Helper Liposomes - Damm, Dominik; Suleiman, Ehsan; Theobald, Hannah; Wagner, Jannik; Batzoni, Mirjam; Kohlhauser, Bianca Ahlfeld Née; Walkenfort, Bernd; Albrecht, Jens Christian; Ingale, Jidnyasa; Yang, Lifei; Hasenberg, Mike; Wyatt, Richard T.; et al. (Pharmaceutics, 2022)
Functionalization of experimental HIV-1 virus-like particle vaccines with heterologous T helper epitopes (T helper VLPs) can modulate the humoral immune response via intrastructural help (ISH). Current advances in the conjugation of native-like HIV-1 envelope trimers (Env) onto liposomes and encapsulation of peptide epitopes into these nanoparticles renders this GMP-scalable liposomal platform a feasible alternative to VLP-based vaccines. In this study, we designed and analyzed customizable Env-conjugated T helper liposomes. First, we passively encapsulated T helper peptides into a well-characterized liposome formulation displaying a dense array of Env trimers on the surface. We confirmed the closed pre-fusion state of the coupled Env trimers by immunogold staining with conformation-specific antibodies. These peptide-loaded Env-liposome conjugates efficiently activated Env-specific B cells, which further induced proliferation of CD4+ T cells by presentation of liposome-derived peptides on MHC-II molecules. The peptide encapsulation process was then quantitatively improved by an electrostatically driven approach using an overall anionic lipid formulation. We demonstrated that peptides delivered by liposomes were presented by DCs in secondary lymphoid organs after intramuscular immunization of mice. UFO (uncleaved prefusion optimized) Env trimers were covalently coupled to peptide-loaded anionic liposomes by His-tag/NTA(Ni) interactions and EDC/Sulfo-NHS crosslinking. EM imaging revealed a moderately dense array of well-folded Env trimers on the liposomal surface. The conformation was verified by liposomal surface FACS. Furthermore, anionic Env-coupled T helper liposomes effectively induced Env-specific B cell activation and proliferation in a comparable range to T helper VLPs. Taken together, we demonstrated that T helper VLPs can be substituted with customizable and GMP-scalable liposomal nanoparticles as a perspective for future preclinical and clinical HIV vaccine applications. The functional nanoparticle characterization assays shown in this study can be applied to other systems of synthetic nanoparticles delivering antigens derived from various pathogens.
CRIS-Team Scopus Importer:2022-07-15
Keywords: coupling mechanism; Env trimer; functionalization; GMP; HIV; immunogold staining; intrastructural help; peptide encapsulation; T helper liposomes; vaccine

Electrostatically driven encapsulation of hydrophilic, non-conformational peptide epitopes into liposomes - Suleiman, Ehsan; Damm, Dominik; Batzoni, Mirjam; Temchura, Vladimir; Wagner, Andreas; Überla, Klaus; Vorauer-Uhl, Karola (Pharmaceutics, 2019)
Since the first use of liposomes as carriers for antigens, much work has been done to elucidate the mechanisms involved in the encapsulation of vaccine-relevant biomolecules. However, only a few studies have specifically investigated the encapsulation of hydrophilic, non-conformational peptide epitopes. We performed comprehensive and systematic screening studies, in order to identify conditions that favor the electrostatic interaction of such peptides with lipid membranes. Moreover, we have explored bi-terminal sequence extension as an approach to modify the isoelectric point of peptides, in order to modulate their membrane binding behavior and eventually shift/expand the working range under which they can be efficiently encapsulated in an electrostatically driven manner. The findings of our membrane interaction studies were then applied to preparing peptide-loaded liposomes. Our results show that the magnitude of membrane binding observed in our exploratory in situ setup translates to corresponding levels of encapsulation efficiency in both of the two most commonly employed methods for the preparation of liposomes, i.e., thin-film hydration and microfluidic mixing. We believe that the methods and findings described in the present studies will be of use to a wide audience and can be applied to address the ongoing relevant issue of the efficient encapsulation of hydrophilic biomolecules.
CRIS-Team Scopus Importer:2019-11-29
Keywords: Electrostatic interactions; Encapsulation; Encapsulation efficiency; Hydrophilic peptides; In situ binding; Liposomes; Microfluidics; Peptide-membrane interaction; Peptides; Vaccines

Genetic co-administration of soluble PD-1 ectodomains modifies immune responses against influenza a virus induced by DNA vaccination - Tannig, Pierre; Peter, Antonia Sophia; Lapuente, Dennis; Klessing, Stephan; Schmidt, Anna; Damm, Dominik; Tenbusch, Matthias; Überla, Klaus; Temchura, Vladimir (Vaccines, 2020)
Due to the low efficacy and the need for seasonal adaptation of currently licensed influenza A vaccines, the importance of alternative vaccination strategies is increasingly recognized. Considering that DNA vaccines can be rapidly manufactured and readily adapted with novel antigen sequences, genetic vaccination is a promising immunization platform. However, the applicability of different genetic adjuvants to this approach still represents a complex challenge. Immune checkpoints are a class of molecules involved in adaptive immune responses and germinal center reactions. In this study, we immunized mice by intramuscular electroporation with a DNA-vaccine encoding hemagglutinin (HA) and nucleoprotein (NP) of the influenza A virus. The DNA-vaccine was applied either alone or in combination with genetic adjuvants encoding the soluble ectodomains of programmed cell death protein-1 (sPD-1) or its ligand (sPD-L1). Co-administration of genetic checkpoint adjuvants did not significantly alter immune responses against NP. In contrast, sPD-1 co-electroporation elevated HA-specific CD4+ T cell responses, decreased regulatory CD4+ T cell pools, and modulated the IgG2a-biased HA antibody pattern towards an isotype-balanced IgG response with a trend to higher influenza neutralization in vitro. Taken together, our data demonstrate that a genetic DNA-adjuvant encoding soluble ectodomains of sPD-1 was able to modulate immune responses induced by a co-administered influenza DNA vaccine.
CRIS-Team Scopus Importer:2020-10-16
Keywords: Checkpoint blockade; DNA adjuvants; DNA vaccine; Immunomodulation; Influenza A; Intramuscular electroporation; Soluble PD-1; Soluble PD-L1

Immunogenicity of Recombinant Lipid-Based Nanoparticle Vaccines: Danger Signal vs. Helping Hand - Temchura, Vladimir; Wagner, Jannik; Damm, Dominik (Pharmaceutics, 2024)
Infectious diseases are a predominant problem in human health. While the incidence of many pathogenic infections is controlled by vaccines, some pathogens still pose a challenging task for vaccine researchers. In order to face these challenges, the field of vaccine development has changed tremendously over the last few years. For non-replicating recombinant antigens, novel vaccine delivery systems that attempt to increase the immunogenicity by mimicking structural properties of pathogens are already approved for clinical applications. Lipid-based nanoparticles (LbNPs) of different natures are vesicles made of lipid layers with aqueous cavities, which may carry antigens and other biomolecules either displayed on the surface or encapsulated in the cavity. However, the efficacy profile of recombinant LbNP vaccines is not as high as that of live-attenuated ones. This review gives a compendious picture of two approaches that affect the immunogenicity of recombinant LbNP vaccines: (i) the incorporation of immunostimulatory agents and (ii) the utilization of pre-existing or promiscuous cellular immunity, which might be beneficial for the development of tailored prophylactic and therapeutic LbNP vaccine candidates.
CRIS-Team Scopus Importer:2024-02-02
Keywords: adjuvants; cellular immunity; heterologous T cell help; immunogenicity; intrastructural help; lipid-based nanoparticles; liposomes; Toll-like receptor ligand; universal T cell epitope; vaccine antigen

Influence of AAV vector tropism on long-term expression and Fc-γ receptor binding of an antibody targeting SARS-CoV-2 - Wagner, Jannik; Müller-Schmucker, Sandra; Wang, Wenjun; Arnold, Philipp; Uhlig, Nadja; Issmail, Leila; Eberlein, Valentina; Damm, Dominik; Roshanbinfar, Kaveh; Enßer, Armin; Oltmanns, Friederike; Peter, Antonia Sophia; et al. (Communications Biology, 2024)
Long-acting passive immunization strategies are needed to protect immunosuppressed vulnerable groups from infectious diseases. To further explore this concept for COVID-19, we constructed Adeno-associated viral (AAV) vectors encoding the human variable regions of the SARS-CoV-2 neutralizing antibody, TRES6, fused to murine constant regions. An optimized vector construct was packaged in hepatotropic (AAV8) or myotropic (AAVMYO) AAV capsids and injected intravenously into syngeneic TRIANNI-mice. The highest TRES6 serum concentrations (511 µg/ml) were detected 24 weeks after injection of the myotropic vector particles and mean TRES6 serum concentrations remained above 100 µg/ml for at least one year. Anti-drug antibodies or TRES6-specific T cells were not detectable. After injection of the AAV8 particles, vector mRNA was detected in the liver, while the AAVMYO particles led to high vector mRNA levels in the heart and skeletal muscle. The analysis of the Fc-glycosylation pattern of the TRES6 serum antibodies revealed critical differences between the capsids that coincided with different binding activities to murine Fc-γ-receptors. Concomitantly, the vector-based immune prophylaxis led to protection against SARS-CoV-2 infection in K18-hACE2 mice. High and long-lasting expression levels, absence of anti-drug antibodies and favourable Fc-γ-receptor binding activities warrant further exploration of myotropic AAV vector-based delivery of antibodies and other biologicals.
CRIS-Team Scopus Importer:2024-07-26

Modulation of immune responses to liposomal vaccines by intrastructural help - Damm, Dominik; Suleiman, Ehsan; Wagner, Jannik; Klessing, Stephan; Pfister, Felix; Elsayed, Hassan; Walkenfort, Bernd; Stobrawe, Jule; Mayer, Julia; Lehner, Elisabeth; Müller-Schmucker, Sandra; Hasenberg, Mike; et al. (European Journal of Pharmaceutics and Biopharmaceutics, 2023)
The encapsulation of HIV-unrelated T helper peptides into liposomal vaccines presenting trimers of the HIV-1 envelope glycoprotein (Env) on the surface (T helper liposomes) may recruit heterologous T cells to provide help for Env-specific B cells. This mechanism called intrastructural help can modulate the HIV-specific humoral immune response. In this study, we used cationic T helper liposomes to induce intrastructural help effects in a small animal model. The liposomes were functionalized with Env trimers by a tag-free approach designed to enable a simplified GMP production. The pre-fusion conformation of the conjugated Env trimers was verified by immunogold electron microscopy (EM) imaging and flow cytometry. The liposomes induced strong activation of Env-specific B cells in vitro. In comparison to previously established anionic liposomes, cationic T helper liposomes were superior in CD4+ T cell activation after uptake by dendritic cells. Moreover, the T helper liposomes were able to target Env-specific B cells in secondary lymphoid organs after intramuscular injection. We also observed efficient T helper cell activation and proliferation in co-cultures with Env-specific B cells in the presence of cationic T helper liposomes. Mouse immunization experiments with cationic T helper liposomes further revealed a modulation of the Env-specific IgG subtype distribution and enhancement of the longevity of antibody responses by ovalbumin- and Hepatitis B (HBV)-specific T cell help. Thus, clinical evaluation of the concept of intrastructural help seems warranted.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Env trimer; Functionalization; HIV vaccine; IgG subtype; Intrastructural help; Nanoparticle; Peptide encapsulation; T helper liposomes

Modulation of vaccine-induced HIV-1-specific immune responses by co-electroporation of PD-L1 encoding DNA - Tannig, Pierre; Peter, Antonia Sophia; Lapuente, Dennis; Klessing, Stephan; Damm, Dominik; Tenbusch, Matthias; Überla, Klaus; Temchura, Vladimir (Vaccines, 2020)
The importance of a balanced TH1/TH2 humoral immune response against the HIV-1 envelope protein (Env) for antibody-mediated HIV-1 control is increasingly recognized. However, there is no defined vaccination strategy to raise it. Since immune checkpoints are involved in the induction of adoptive immunity and their inhibitors (monoclonal antibodies) are licensed for cancer therapy, we investigated the effect of checkpoint blockade after HIV-1 genetic vaccination on enhancement and modulation of antiviral antibody responses. By intraperitoneal administration of checkpoint antibodies in mice we observed an induction of anti-drug antibodies which may interfere with immunomodulation by checkpoint inhibitors. Therefore, we blocked immune checkpoints locally by co-electroporation of DNA vaccines encoding the active soluble ectodomains of programmed cell death protein-1 (PD-1) or its ligand (PD-L1), respectively. Plasmid-encoded immune checkpoints did not elicit a detectable antibody response, suggesting no interference with their immunomodulatory effects. Co-electroporation of a HIV-1 DNA vaccine formulation with soluble PD-L1 ectodomain increased HIV-1 Env-specific TH1 CD4 T cell and IgG2a antibody responses. The overall antibody response was hereby shifted towards a more TH1/TH2 balanced subtype pattern. These findings indicate that co-electroporation of soluble checkpoint ectodomains together with DNA-based vaccines has modulatory effects on vaccine-induced immune responses that could improve vaccine efficacies.
CRIS-Team Scopus Importer:2020-02-04
Keywords: Checkpoint blockade; Checkpoint inhibitors; HIV-1; Immunomodulation; Intramuscular electroporation; Soluble immune checkpoints

Oriented display of HIV-1 Env trimers by a novel coupling strategy enhances B cell activation and phagocytosis - Di Vincenzo, Riccardo; Beutel, Jannis; Arnold, Philipp; Wang, Yu; Damm, Dominik; Tannig, Pierre; Lux, Anja; Temchura, Vladimir; Eichler, Jutta; Überla, Klaus (Frontiers in Immunology, 2024)
Introduction: Conformationally stabilized Env trimers have been developed as antigens for the induction of neutralizing antibodies against HIV-1. However, the non-glycosylated immunodominant base of these soluble antigens may compete with the neutralizing antibody response. This has prompted attempts to couple Env trimers to organic or inorganic nanoparticles with the base facing towards the carrier. Such a site-directed coupling could not only occlude the base of the trimer, but also enhance B cell activation by repetitive display. Methods: To explore the effect of an ordered display of HIV-1 Env on microspheres on the activation of Env-specific B cells we used Bind&Bite, a novel covalent coupling approach for conformationally sensitive antigens based on heterodimeric coiled-coil peptides. By engineering a trimeric HIV-1 Env protein with a basic 21-aa peptide (Peptide K) extension at the C-terminus, we were able to covalently biotinylate the antigen in a site-directed fashion using an acidic complementary peptide (Peptide E) bearing a reactive site and a biotin molecule. This allowed us to load our antigen onto streptavidin beads in an oriented manner. Results: Microspheres coated with HIV-1 Env through our Bind&Bite system showed i) enhanced binding by conformational anti-HIV Env broadly neutralizing antibodies (bNAbs), ii) reduced binding activity by antibodies directed towards the base of Env, iii) higher Env-specific B cell activation, and iv) were taken-up more efficiently after opsonization compared to beads presenting HIV-1 Env in an undirected orientation. Discussion: In comparison to site-directed biotinylation via the Avi-tag, Bind&Bite, offers greater flexibility with regard to alternative covalent protein modifications, allowing selective modification of multiple proteins via orthogonal coiled-coil peptide pairs. Thus, the Bind&Bite coupling approach via peptide K and peptide E described in this study offers a valuable tool for nanoparticle vaccine design where surface conjugation of correctly folded antigens is required.
CRIS-Team Scopus Importer:2024-03-01
Keywords: antigen display; B cell activation; HIV-1; neutralizing antibodies; peptides; phagocytosis